Leading Through Teachers’ Eyes: Lived Experiences and Perceptions of Teachers on School Leadership Practices in Public Elementary Schools - Lasier Guinumtad (International Journal of Education, Literacies and Curriculum Studies, 2026)
School leadership is experienced most directly by teachers through everyday interactions, administrative decisions, instructional support, professional development, communication, and workplace relationships. Understanding leadership from teachers’ perspectives therefore provides important insights into how formal leadership practices are translated into everyday school experiences. This qualitative phenomenological study explores the lived experiences and perceptions of teachers regarding school leadership practices in public elementary schools in Mayoyao District, Ifugao, Philippines. Specifically, it examines how teachers experience leadership in relation to instructional support, communication and decision-making, professional development, recognition and motivation, interpersonal relationships, and responses to contextual challenges. Participants are purposively selected public elementary school teachers with sustained experience working under school-level leadership. Data are generated through semi-structured, in-depth interviews and analyzed using Colaizzi’s descriptive phenomenological method. The inquiry is sensitized by contemporary perspectives on instructional, transformational, and distributed leadership and by the Philippine Professional Standards for School Heads (PPSSH), while allowing themes to emerge from participants’ accounts. The study positions teachers not merely as recipients of leadership decisions but as knowledgeable organizational actors whose experiences reveal how leadership is enacted, negotiated, and interpreted within rural elementary-school contexts. Findings are expected to contribute to culturally and contextually responsive leadership development, teacher–leader relationships, professional support mechanisms, and school-improvement initiatives in geographically situated public-school communities.